Distribution of an increasing roe deer population in a fragmented Mediterranean landscape - Tellería, José Luis; Virgós, Emilio (Ecography, 1997)
This paper describes roe deer Capreolus capreolus distribution in central Spain, where the species has spread from the mountains into peripheral agricultural areas In this region, it is more abundant in forest fragments near the mountains than in those further away, in pine and oak woodlands than in sclerophyllous forests, and in forests with open water than in those lacking this resource The paper also analyzes whether habitat quality and geographic location of forests with respect to roe deer source areas are the two basic causes of its distribution, as predicted by some models of the species distribution in fragmented landscapes The results corroborate this hypothesis revealing that roe deer abundance is linked negatively to sclerophyllous forest cover and distance from mountains We conclude that this type of farmland seems to be sub-optimal for roe deer in comparison with forested, moist mountains
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: abundance; Distribution patterns; forest cover; habitat quality (voyant); roe deer

Distribution of an increasing roe deer population in a fragmented Mediterranean landscape (Ecography, 1997)
This paper describes roe deer Capreolus capreolus distribution in central Spain, where the species has spread from the mountains into peripheral agricultural areas In this region, it is more abundant in forest fragments near the mountains than in those further away, in pine and oak woodlands than in sclerophyllous forests, and in forests with open water than in those lacking this resource The paper also analyzes whether habitat quality and geographic location of forests with respect to roe deer source areas are the two basic causes of its distribution, as predicted by some models of the species distribution in fragmented landscapes The results corroborate this hypothesis revealing that roe deer abundance is linked negatively to sclerophyllous forest cover and distance from mountains We conclude that this type of farmland seems to be sub-optimal for roe deer in comparison with forested, moist mountains